2006
DOI: 10.1002/eji.200636347
|View full text |Cite
|
Sign up to set email alerts
|

Temporal cross‐talk between TCR and STAT signals for CD8 T cell effector differentiation

Abstract: The strength and duration of signaling through surface receptors is a primary means of controlling cell fate decisions. In adaptive immunity, Ag‐initiated T cell stimulation is secondarily regulated by cytokines. We here summarize evidence for temporal control of a gene expression program in naive CD8 T cells. It is initiated in response to TCR engagement but relies on secondary signaling from cytokine receptors to be sustained and to allow development of full effector capacity. This mechanism permits cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 90 publications
2
28
0
Order By: Relevance
“…1B). This pattern of gene expression is consistent with a role for STAT5 in the stabilization of a Tc1 gene expression program initiated by TCR stimulation (33,34).…”
Section: Stat5ca Expression In In Vivo-transferred Cd8 T Cells Inducesupporting
confidence: 84%
See 2 more Smart Citations
“…1B). This pattern of gene expression is consistent with a role for STAT5 in the stabilization of a Tc1 gene expression program initiated by TCR stimulation (33,34).…”
Section: Stat5ca Expression In In Vivo-transferred Cd8 T Cells Inducesupporting
confidence: 84%
“…Whether a relationship of causality exists between early expression of some of the genes from type 1 cluster and subsequent expression of some genes of the type 2 cluster remains to be determined. The pattern of expression of the type 1 gene cluster, including Tbx21/Tbet, is consistent with a role for STAT5CA in the stabilization of a Tc1 gene expression program initiated by TCR stimulation (33,34). For Eomes expression, STAT5CA appeared to induce a timedependent accumulation of the transcripts (type 2 cluster).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…STAT5 and TCR signaling pathways are reported to synergize during T cell activation by Ag (72)(73)(74). We have shown that IL-21, which signals mainly via STAT3 (14,75), enhances the phosphorylation of STAT5 induced by IL-15 in naive CD8 T cells (14).…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown in several studies that naive CD8 T cells require only a brief antigenic stimulation to develop full effector function and transit into memory. However, the validity of this concept has been questioned (29,30). More recently, two groups (21,31) have reported the phenotypic and functional difference between CD8 T cells responding to short-lived vs prolonged infection.…”
Section: Discussionmentioning
confidence: 99%